Edukasi Pembuatan Video Media Pembelajaran Paud Menggunakan Komputer Bagi Tenaga Pendidik PAUD Lilik Kecamatan Bukit Raya - Roki Hardianto; Wirdah Choiriah; Fana Wiza (Fakultas Ilmu Budaya Universitas Lancang Kuning, 2021)
In this activity, educators at the Lilik PAUD School which is located at Air Cold Village, Bukit Raya District, Pekanbaru City are taught about making learning media in the form of computer-enabled videos. So far, educators have used learning media manually by utilizing cardboard and pictures made independently by the teacher. During the Covid-19 pandemic, teachers had difficulties in making learning media that could be applied in online learning. This activity was initiated by the Association of Indonesian Early Childhood Educators and Education Personnel (HIMPAUDI) Bukit Raya District. The output of this activity is in the form of products made by training participants, scientific journals of activity results, news of activities published on online media and teaching modules that can be used by teachers.